Knowledge management in the Malaysian armed forces: a study on perceptions and applications in the context of an information and communication technology environment / Ismail Manuri - Manuri, Ismail (2012)
The development of modern warfare is reflected by the rising importance of having knowledge advantage over adversaries. Leadership, sense making, problem solving and decision-making are more complex and more demanding in military situations. Command and control is taking on new dimensions, and the role of military personnel is evolving into that of 'thinking soldier'. The "information superiority" becomes the determinant of the future war management and requires a drastic improvement in information management, assurance, exchanging and sharing of superior knowledge. The aim of the study is to examine the attitude of the MAF officers' towards Knowledge Management 'that include knowledge creation, Knowledge Management processes, Knowledge Management applications, and technology. Five hypotheses were developed in order to examine the degree of statistical significant difference in perceptions towards Knowledge Management. "The results of the study showed that, the perceptions towards knowledge creation, Knowledge Management processes, Knowledge Management applications and technology by the MAF officers were not significantly different. However, there is a statistical significant difference in perceptions towards knowledge creation based on respondent's rank, academic background, and working experience. The perceptions towards technology were only significantly different based on the respondent's academic background. Further, the results showed that a positive correlation existed between Knowledge Management applications and Knowledge Management processes, and technology. There was also a positive relationship between technology and knowledge creation, and Knowledge Management processes. Further analysis on the Knowledge Management applications, the results demonstrated a relatively low Knowledge Management practices in the MAF due to lack of exposure and awareness among the MAF personnel.